IMPLEMENTASI NILAI-NILAI KARAKTER DALAM PEMBELAJARAN GEOGRAFI PADA KELAS X D MAN 1 PROBOLINGGO - Juwaeni; Firdaus , Silvi Aldinta (Madani : Journal of Social Sciences and Social Science Education, 2023)
This research aims to determine character values in geography subjects at MAN 1 Probolinggo. The research method used is a qualitative descriptive method with data collection techniques in the form of observation and documentation. The research sample using purposive sampling was class X D MAN 1 Probolinggo. Testing the validity of the data used in this research is the source triangulation technique. Analysis of the data obtained was carried out in several stages, namely data collection, data reduction, data presentation, and verification/drawing conclusions. The research results show that character values in geography subjects are integrated into the Teaching and Learning Activities (KBM) process with a learning method approach that supports the strengthening of interactive and participatory character education, or by directly observing the characters in the school environment. The application of character values to students seems to have experienced positive changes and significant improvements as a reflection of the results of the application of character values which are reflected in students who are moral, positive and responsible.